Interprofessional Education (IPE) - Alotaibi, Naif Munif Aldumayki; Alharbi, Saleh Helayyil Saleh; Alghofaily, Faisal Mohammed; Barak, Talal Mohammed Nahs Bin; Al-Khaldi, Nahar Khalif; Barak, Talal Muhammad Bin; Alanazi, Ali Jamal (International journal of health sciences, 2024)
Background: Interprofessional Education (IPE) has emerged as a pivotal strategy in addressing the fragmented nature of healthcare delivery. By fostering collaboration among disciplines such as Pharmacy, Nursing, and Medical Laboratory Science, IPE bridges gaps in communication, enhances teamwork, and improves patient outcomes. Despite its recognized potential, the integration of IPE into healthcare education faces challenges related to implementation, sustainability, and evaluation. Aim: This paper aims to explore the theoretical underpinnings, implementation strategies, and outcomes of IPE programs, with a focus on their impact on interdisciplinary collaboration among Pharmacy, Nursing, and Medical Laboratory professionals. Methods: A systematic review of recent studies, case reports, and institutional initiatives was conducted to evaluate the effectiveness of IPE. Data were collected from peer-reviewed journals, healthcare education reports, and surveys. Key metrics included improvements in teamwork, patient safety, and professional competency. Qualitative data from case studies and participant interviews were also analyzed to capture experiential insights. Results: Findings indicate that IPE significantly enhances interdisciplinary communication and reduces errors in patient care. Participants reported increased understanding of roles and responsibilities across professions. Case studies highlighted successful implementation of IPE in both academic and clinical settings, though challenges such as logistical barriers and resistance to change persist.